Knowledge transfer between european universities through the Erasmus students programme - Martins, Dora (2017)
The European Commission presents the Erasmus+ Programme as a tool to achieving economic growth and creating highly-skilled jobs in Europe, in order to strengthen its position as a knowledge-based economy. This programme aims to improve the quality and relevance of higher education, strengthening quality through mobility and cross-border cooperation, making the knowledge triangle work: linking higher education, research and business to achieve excellence and bring about regional development, and therefore improving governance and funding. The aim of this work is to analyse and understand the Erasmus+ student's expectations that choose a Portuguese higher education institution to perform their Erasmus+ experience. Semi-structure interviews were conducted to obtain qualitative data. Twenty eight Erasmus+ students (twenty female and eight male) with mean age of 25 years (SD= 6,3). The data were analysed according to content analysis procedures. The main results showed that the motivations to have an Erasmus+ experience were the need to learn another language and add cultural background to their personal experience. It is also understood as a good way to develop their knowledge in academic and personal learning, and to promote their employability. Erasmus+ students believe that their curriculum vitae is valued, gaining more flexibility and more competence to work in the international environment. Their expectations are to improve the domain of a foreign language, to increase personal and professional independence, to ameliorate academic and communication skills, and to have more responsibility and comprehension about professional environments. The return to the home country is also referred as a relevant moment in this experience. Students expect to be more confident in that occasion, to have more personal and professional skills that facilitate their employability. In conclusion, our results suggest that Erasmus+ students believed that this experience is an important way to develop personal and professional knowledge and fundamental skills to their employability. These results reinforce the relevance and the need to invest in Erasmus+ project because this seems to be an important tool to ameliorate student's skills and promote their employability.